Jejak Aspirasi: Program Alumni Smi Addimyati dalam Menguatkan Karakter Akhlak Berbahasa Al-Qur’an pada Remaja - Ery Subaeri Ahmad; Rini Nuraini; Solikhul Hadi; Wiwi Uswatiyah; Husnul Khotimah; Dwi Rahmah Nur Hafizah; Banu Aji Ismail (Jurnal Dirosah Islamiyah, 2026)
This research focuses on the "Jejak Aspirasi" program initiated by the alumni of SMI Addimyati as an innovation to strengthen the moral character (akhlak) of adolescents through the habituation of Qur’anic language. The primary objective of this study is to gain an in-depth understanding of how SMI Addimyati alumni design, implement, and evaluate the "Jejak Aspirasi" program in internalizing Qur’anic language as a foundation for noble character building among teenagers. The research method employed is qualitative with a field study approach. Data were collected through in-depth interviews with alumni board members and program participants, direct observation of activities, and documentation. The results indicate that this program not only successfully enhances adolescents' skills in applying Qur’anic language in daily communication but also fosters religious attitudes, discipline, responsibility, and social concern. The presence of alumni as mentors and role models has a significant impact on participant motivation. Furthermore, this study finds that the success of "Jejak Aspirasi" lies in the synergy between alumni, the school, and the adolescents themselves, creating a conducive environment for the internalization of Qur’anic values. This program can serve as an alumni-based moral development model that is relevant and applicable in various Islamic educational institutions. Thus, "Jejak Aspirasi" proves that alumni contributions extend beyond the academic realm and play a strategic role in strengthening adolescent character to remain steadfast in following the Al-Qur’an as a guide for life.